2018
DOI: 10.1021/acs.analchem.8b04823
|View full text |Cite
|
Sign up to set email alerts
|

TiO2/g-C3N4/CdS Nanocomposite-Based Photoelectrochemical Biosensor for Ultrasensitive Evaluation of T4 Polynucleotide Kinase Activity

Abstract: Herein, an efficient photoelectrochemical (PEC) platform was constructed by a cosensitization strategy with a cascade energy level arrangement for the ultrasensitive evaluation of T4 polynucleotide kinase (T4 PNK). Based on CdSe quantum dots (QDs) with an extremely narrow bandgap, this cosensitization strategy offered a highly efficient sensitizer with a matching band-edge level of a ternary TiO2/g-C3N4/CdS nanocomposite. In this protocol, the ternary nanocomposite was first prepared to serve as the matrix to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…While generating photogenerated electrons, the photogenerated holes are left in the valence band of g-C3N4 and CdS, respectively. Because the valence band of g-C3N4 is more positive than that of CdS, the holes of the g-C3N4 valence band can easily move to the valence band of CdS [70][71][72]. Consequently, the composite of g-C3N4 and CdS deposited on TiN substrate can significantly enhance the photoelectrocatalytic performance due to the effective separation of electron-hole pairs and broadening of the light absorption range.…”
Section: Resultsmentioning
confidence: 99%
“…While generating photogenerated electrons, the photogenerated holes are left in the valence band of g-C3N4 and CdS, respectively. Because the valence band of g-C3N4 is more positive than that of CdS, the holes of the g-C3N4 valence band can easily move to the valence band of CdS [70][71][72]. Consequently, the composite of g-C3N4 and CdS deposited on TiN substrate can significantly enhance the photoelectrocatalytic performance due to the effective separation of electron-hole pairs and broadening of the light absorption range.…”
Section: Resultsmentioning
confidence: 99%
“…The rapidly increased photocurrent is detected in "trace b" (from 10 to 30 s) due to decrease in the rate of electron-hole recombination and the high-efficiency absorption. In the TiO2/g-C3N4 modified-FTO in "trace c", the photocurrent increases to 30.7 μA since the bandgap of the g-C3N4 reduces the charge carrier recombination and facilitates the electron transmission [557]. The photocurrent increases in "trace d" (TiO2/g-C3N4/CdS nanocomposite-modified electrode).…”
Section: Sensorsmentioning
confidence: 99%
“…Like other applications, g-C 3 N 4 -TiO 2 based structures are one of the most used composites for sensing applications. Li et al demonstrated that the photoelectrochemical TiO 2 /g-C 3 N 4 /CdS platform could be employed for the ultrasensitive determination of T4 polynucleotide kinase (T4 PNK) because this composite showed significant stability and reproducibility with high selectivity [557]. The photocurrent response is demonstrated in Figure 21A.…”
Section: Sensorsmentioning
confidence: 99%
See 2 more Smart Citations